2019
DOI: 10.17265/1934-8975/2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thickness of Polymer Electrolyte Membrane and Gas Diffusion Layer on Temperature Distributions in Polymer Electrolyte Fuel Cell Operated at Temperature around 90 °C

Abstract: Polymer Electrolyte Fuel Cell (PEFC) is desired to be operated at temperature around 90 °C for stationary applications during the period from 2020 to 2025 in Japan. It can be expected thinner polymer electrolyte membrane (PEM) and gas diffusion layer (GDL) would promote the power generation performance of PEFC at this temperature. The aim of this study is to understand the impact of thickness of PEM and GDL on the temperature profile of interface between PEM and catalyst layer at the cathode (i.e., the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…W E indicates the electric work produced by PEFC. E i and W E are defined as following [24] [25] [26] [27]:…”
Section: Heat Generation Rate By Reaction In the Model Proposed By Th...mentioning
confidence: 99%
See 3 more Smart Citations
“…W E indicates the electric work produced by PEFC. E i and W E are defined as following [24] [25] [26] [27]:…”
Section: Heat Generation Rate By Reaction In the Model Proposed By Th...mentioning
confidence: 99%
“…A few researchers [4] [22] [23] have reported numerical simulation on temperature distribution in a single PEFC which is operated at a higher temperature than usual. However, only a few papers [4] [22] have investigated the tempera-ture distribution on the interface between PEM and electrode at the cathode, which is defined as the reaction surface in this study, excluding the research conducted by the authors [24] [25] [26] [27]. The previous studies [24] [25] [26] [27] have confirmed the thickness effect of not only PEM but also GDL on the distribution of temperature at reaction surface (T react ) in a single PEFC at a higher temperature, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, in order to improve the efficiency of the flow characteristics inside the GDL, various studies have been carried out from the viewpoint of the design such as the clamping pressure that is produced in the stack assembly process, the assembling method and the optimum structural design method [7,8]. These studies aim to control the material characteristics and the design variables of fuel cells, such as hydrophobic polymer content [9,10], pore-size distribution [11,12], temperature distribution [13], humidity, differential pressure effects and compressive force effects of GDLs [14][15][16][17][18][19][20][21][22][23]. The amount of compression ratio of the GDL affects the porosity, directionality and the fraction of the pore space occupied by liquid water and affects the performance of a fuel cell.…”
Section: Introductionmentioning
confidence: 99%